Inequality and its correlation with economic development on African economies, with a focus on South Africa - Wollentine, Brandon (2023)
Inequality is often a word which has more social rather than economic connotations, despite it having many relevant economic applications. Whilst many other theories and factors are examined with relations to how economies develop and grow, inequality is not one which is usually at the forefront of consideration. Numerous pieces of research have been conducted on just how and why inequality occurs, but often the long-term developmental aspects, and long-term causes of inequality throughout Africa are not considered extensively. Other developmental factors are often attributed as to why or why not African economies have grown or have failed to grow in the manner in which they have the potential to. By examining inequality as a whole, this thesis aims to delve deeper into just how significant inequality is on developing economies in Africa, and why these reasons were caused, and in many cases still persist. To better understand both the causes and outcomes of inequality in African economies, and specifically South Africa, this thesis will analyse the manner in which inequality has risen through these economies and how it has hindered and can potentially hinder future economic development. This thesis will utilise primarily qualitative research in the form of a literature review and a theoretical analysis, as well as a quantitative approach, with a data analysis being employed, to better comment on how or why certain levels of inequality occur and why and how they affect economic development. This thesis aims to contribute to the literature on a relevant topic, exploring the role that inequality has to play with regards to the broader perspective of economic development in Africa economies, and specifically South Africa. Its findings aim to inform and encourage further research on inequality on a macroeconomic level, as well as to encourage more research on the importance of creating equal societies to foster positive economic change.